Nitrogen Dopants in Carbon Nanomaterials: Defects or a New Opportunity?. Issue 1 (12th December 2016) - Lee, Won Jun; Lim, Joonwon; Kim, Sang Ouk
Abstract : Substitutional N‐doping of carbon nanomaterials refers to the chemical functionalization method that replaces a part of the carbon atoms in fullerene, carbon nanotubes, or graphene by nitrogen. N‐doping has attracted a tremendous amount of research attention for their unique possibilities, spanning from its ability to engineer various physiochemical properties of carbon nanomaterials in a stable manner with different dopant configurations. Many viable configurations of N‐dopants are accompanied by typical structural defects, while still preserving the structural symmetry in the basal graphitic plane. Here, the physicochemical features are highlighted and the exciting challenges of N‐dopants in carbon nanomaterials identified, with particular emphasis on the broad tunability of the material properties and relevant emerging applications. Abstract : Pioneering studies of nitrogen‐doped carbon nanomaterials, including carbon nanotubes and graphene, are discussed and highlighted, guided by new insight into the physics and chemistry of materials. This brief review of pivotal concepts and perspectives on the next steps forward is sufficient to appreciate the great potential of nitrogen doping: turning the defects into new opportunities.